Economic evaluation of a publicly funded hepatitis A travel vaccination program in Ontario, Canada. Issue 11 (7th March 2019) - Ramsay, L.C.; Anyiwe, K.; Li, M.; Macdonald, L.; Coyte, P.C.; Sander, B.
Highlights: A publicly funded hepatitis A vaccination program not found to be cost-effective. The model was most sensitive to the risk of hepatitis A infection while traveling. Model would benefit from better understanding of risks and travel characteristics. Abstract: Background: Hepatitis A virus (HAV) causes acute liver infection and is spread through the fecal-oral route. Travel to countries in HAV-endemic regions (e.g., Asia and Latin America) is a well-described risk factor for infection. Currently, Ontario publicly funds hepatitis A vaccination for some populations at high risk of HAV infection but not for all travellers to endemic countries. The objective of this study was to determine the cost-effectiveness of expanding publicly funded HAV vaccination to people planning travel to HAV-endemic regions, from the Ontario healthcare payer perspective. Methods: We conducted a cost-utility analysis comparing an expanded high-risk publicly-funded hepatitis A vaccination program including funded vaccine for travellers to endemic regions to the current high risk program in Ontario. A Markov state transition model was developed, including six possible health states. Model parameters were informed through targeted literature searches and included hepatitis A disease probabilities, utilities associated with health states, health system expenditures, and vaccine costs. Future costs and health outcomes were discounted at 1.5%. Primary outcomes included cost, incremental cost-effectiveness ratio (ICER) and quality adjusted life years (QALYs) over a lifetime time horizon. We conducted one-way, two-way, and probabilistic sensitivity analysis. Results: The expanded high risk HAV vaccine program provided few incremental health gains in the travel population (mean 0.000037 QALYs/person), at an incremental cost of 124.31. The ICER of the expanded program compared to status quo is 3, 391, 504/QALY gained. The conclusion of the model was robust to changes in key parameters across reasonable ranges. Conclusions: The expanded vaccination program substantially exceeds commonly accepted cost-effectiveness thresholds. Further research concerning possible cost-effective implementation of high-risk travel hepatitis A vaccination should focus on a more integrated understanding of the risk of acquiring hepatitis A during travel to endemic regions (e.g., purpose, length of stay).